Proposta de integração entre balanced scorecard e business intelligence - Pardo, Caio Gomes Leo (Universidade Federal de São Carlos, 2020)
This study aims to propose a model for integrating the Balanced Scorecard with Business Intelligence through an analysis of the literature on the topic and subsequent suggestion of steps for building and using both tools together. The literature on the association of BSC and BI focuses on the advantages and consequences of integration, as well as particular characteristics of applications in specific contexts. The study described here focuses on the possible competitive advantages of using an integrated system and the complementary aspects between the tools. For the literature review, the systematic review method has been used, which includes: the planning stage, which defines the terms that will be searched in the databases; the driving stage, when the search expressions are built; and finally, the results, which consists on making a list of the texts found. Subsequently, a theoretical framework has been constructed with the main contributions of the texts resulted from the review. Based on the readings performed and the theoretical framework, the main objective has been constructed: the definition of the steps to be followed for the structuration of an integrated system that achieves the advantages indicated considering more generic contexts.
Integration proposal between balanced scorecard and business intelligence
Keywords: Balanced scorecard; Business intelligence; BSC; BI; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS